Pembelajaran Bahasa Arab di Mi Era Digital - Adinda Nadda Namira; Sapri Sapri; Khatulistiwa Khatulistiwa; Laila Khairani Nasution; Salsa Fadilla; Nurul Dinda Aulia; Suci Pitri Yana; Wayana Anisa Damanik (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The all-digital era has made digital media a source and learning platform that can be used anywhere and at any time. The convenience of this technology makes learning even easier to access. Because through online distance learning pupils or students can meet teachers without face to face. This research uses a literature study method by researching journals that discuss matters related to learning in the digital era. The aim of this research is to analyze developments that have occurred in the digital era in Arabic language learning using digital applications. The results of this research are that the development of Arabic language education in the digital era has brought great progress. Digital learning materials enrich students' learning experience through engaging and flexible content